Selective Nitrations of 2-(1'-Phenylpyrazol-4'-yl) Benzimidazoles: Nitrations of Pyrazoles (Biological Sciences - PJSIR, 2009)
Nitration of 2-(1'-phenylpyrazol-4'-yl) benzimidazole ring system was found to be temperature dependent. Room temperature nitration occurred at the phenyl ring of pyrazole, while at 100 °C, a dinitrated product is obtained where the second nitro group is introduced at the 5-position of the benzimidazole ring. Nitration at 100 °C leads directly to the expected dinitration product. Mass spectral fragmentations for both the compounds is described.